Nebulized CLODOS Technology Shows Clear Virucidal Properties against the Human Coronavirus HCoV-229E at Non-Cytotoxic Doses - Sabina Andreu; Inés Ripa; Raquel Bello-Morales; José Antonio López-Guerrero (Viruses, 2021)
The emergent human coronavirus SARS-CoV-2 and its high infectivity rate has highlighted the strong need for new disinfection systems. Evidence has proven that airborne transmission is an important route of spreading for this virus. Therefore, this short communication introduces CLODOS Technology®, a novel strategy to disinfect contaminated surfaces. It is a product based on stable and 99% pure chlorine dioxide, already certified as a bactericide, fungicide and virucide against different pathogens. In this study, CLODOS Technology®, by direct contact or thermonebulization, showed virucidal activity against the human coronavirus HCoV-229E at non-cytotoxic doses. Different conditions such as nebulization, exposure time and product concentration have been tested to standardize and optimize this new feasible method for disinfection.